Pengembangan E-Modul Terintegrasi Literasi Sains melalui Pendekatan Deep Learning pada Pokok Bahasan Ikatan Kimia - Dina Amelia Tambunan; Destria Roza (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The low level of students' understanding of concepts and scientific literacy in chemical bonding material indicates the need for teaching materials that can facilitate meaningful learning. This study aims to develop an integrated e-module of scientific literacy through a deep learning approach in chemical bonding material, as well as to determine the level of feasibility, improvement in learning outcomes, and student responses to the developed product. The study used the Research and Development (R&D) method with a 4D model that includes define, design, develop, and disseminate. The research subjects consisted of three validators and 36 students of grade X of SMA Negeri 1 Deli Tua, Deli Serdang, North Sumatra. The research instruments were validation sheets, learning outcome tests, and student response questionnaires. The results showed that the e-module obtained a feasibility percentage of 88.93% from material experts, and 89.44% from media experts with a very valid category. The use of the e-module resulted in an increase in learning outcomes with an N-Gain value of 0.72 (high category), and obtained a student response of 83.31% (positive category). Thus, the integrated e-module on scientific literacy through a deep learning approach is suitable for use as a teaching material to support learning about chemical bonds.